UPAYA MENINGKATKAN KETERAMPILAN MENULIS PUISI KEINDAHAN ALAM MELALUI MEDIA ALAM SEKITAR PADA SISWA KELAS V SDN 05 RIWANG KABUPATEN LUWU - Ratna Ratna (Journal of Teaching dan Learning Research, 2019)
This study aims to determine the improvement of poetry writing skills by using natural media around fifth grade students at SDN 05 Riwang, Larompong District, Luwu District. This research is a classroom action research consisting of two cycles with the stages of Planning, Implementation, Observation and Reflection. The subject of this research is the fifth grade students in the odd semester of 2017/2018 school year with 20 students. Sources of data in this study are primary data and secondary data. Data collection tests were carried out using interviews, observations, and tests of processing techniques and data analysis used, namely quantitative data analysis and qualitative data analysis. The results of the study showed that the use of natural media around the poetry of natural beauty has increased each cycle. which carried out as many as two cycles showed that the completeness of student learning outcomes, Indonesian subjects poetry material of natural beauty has increased, the average value in cycle I was 75 with completeness 80%, and increased in cycle II which is 95 with 100% completeness, It can be concluded that, using natural media around will help a teacher in carrying out learning activities and students will be easier to understand, so that students at SDN 05 Riwang, Larompong District, Luwu Regency, can improve learning outcomes.